Challenges of Religious Moderation Through Islamic Religious Education in Junior High Schools: A Systematic Literature Review - Islahuddin, M.; Rosyidah, Aisyatur; Arifin, Syamsul; Humaidi, M.N.; Romelah, Romelah (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Religious moderation has become an important educational agenda in Indonesia, particularly in strengthening tolerance, non-violence, national commitment, and respect for diversity among students. At the junior high school level, Islamic Religious Education plays a strategic role in introducing and internalizing moderation values. However, previous studies indicate that the implementation of religious moderation in schools still faces various challenges. This study aims to systematically review previous research on the challenges of religious moderation through Islamic Religious Education in junior high schools and to develop a conceptual framework based on recurring findings. This study employed a Systematic Literature Review approach guided by the PRISMA framework. The literature search was conducted using Publish or Perish to retrieve records from Google Scholar and Scopus for the 2020–2026 publication period. From 1,887 initially identified records, 9 articles met the inclusion criteria and were included in the final synthesis. The findings show that the challenges of religious moderation through Islamic Religious Education are shaped by three interconnected dimensions: school policy and institutional support, religious understanding, and socio-digital dynamics. These challenges include limited curriculum integration, insufficient learning resources, limited religious moderation literacy, differences in teachers’ and students’ religious understanding, limited dialogical learning practices, and the need for technology-based learning media in responding to students’ socio-digital contexts. This review contributes a structured conceptual framework that clarifies how institutional, pedagogical, religious, and digital factors interact in the implementation of religious moderation through Islamic Religious Education in junior high schools.